VD_FINDINFO AF 2/09 - 5/2009 vom 13. Oktober 2009 - VD Tribunal cantonal (2009)
ALLOCATION FAMILIALE | 56 al. 1 LPGA, 58 LPGA, 60 al. 1 LPGA, 2 LPA-VD, 93 al. 1 let. a LPA-VD, 94 al. 1 let. a LPA-VD, 4 al. 1 LAFam, 4 LAFam, 7 al. 1 LAFam, 8 LAFam, 3 al. 1 LVLAFam, 3 al. 2 LVLAFam, art. 1 al. 2 RLVLAFam